Pengaruh Kualitas Produk, Harga dan Promosi Terhadap Keputusan Pembelian Mahasiswa Ponorogo di Marketplace Lazada - Diah Eka Intan Pratiwi; Ely Masykuroh (Institut Agama Islam Negeri Ponorogo, 2023)
The Lazada application is a Singapore private Marketplace application founded by Rocket Internet in 2011. Lazada is an online shopping center that offers various types of products. The decision to purchase has several considerations regarding product quality, price, place, and promotions offered. This purchase decision stage is an evaluation stage by consumers to buy the preferred product brand. This quantitative research aims to answer whether there is a positive influence between product quality, price, and promotion on purchasing decisions on the Lazada Marketplace. To test and analyze Product Quality, Price, and Promotion on consumer purchasing decisions on the Lazada Marketplace. The research method used is quantitative by collecting primary data through the survey method by distributing questionnaires to 100 Ponorogo students. The analytical method used is multiple linear regression. Hypothesis testing is done by statistical tests, namely the t-test (partial) and the F-test (simultaneous). The results of this study are based on the partial test (t-test) showing that the product quality variable has a positive effect on purchasing decisions. This can be seen from the t count of 2.250 with a sig value of 0.027. Based on the partial test (t-test) shows that the price variable has a positive effect on purchasing decisions on the Lazada Marketplace. This can be seen from the t count of 2.428 with a sig value of 0.017. Based on the partial test (t-test) shows that the promotion variable has a positive effect on purchasing decisions on the Lazada Marketplace. This can be seen from the t count of 3.198 with a sig value of 0.002. The F test results show that the variable product quality, price, and promotion positively and significantly influence purchasing decisions on the Lazada Marketplace. This can be seen from the acquisition of F count 37.264 with a sig value of 0.000.